Gambaran depresi dan faktor yang memengaruhi pada remaja yatim piatu di Denpasar - Wetarini, Krisnhaliani; Jaya Lesmana, Cokorda Bagus (E-Jurnal Medika Udayana, 2018)
Depression among orphaned teenagers is a vulnerable mental health disorder that occurs as an impact of the absence of an adequate relationship and affection from parents since childhood period. Cross-sectional analytical study was carried out, enrolling 93 orphaned teenagers from three orphanages in Denpasar City. Sociodemographic data were obtained using questionnaires and level of depression were classified based on Beck’s Depression Inventory. The level of depression among orphaned teenagers respectively, normal (60.2%), mild depression (18.3%), moderate depression (15.1%), and severe depression (6.5%). Logistic regression analysis showed that the only sociodemographic factor that significantly related to depression is gender, boys were about 39% less-likely to experience depression than girls (OR=0.39; p=0.03). Depression is prevalent among girl orphans, thus counseling and social support are needed to overcome the occurrence of depression among orphaned teenagers in Denpasar. Keywords: depression, teenager, orphans